Electronic word of mouth dan kualitas informasi terhadap keputusan pembelian produk halal di TikTok shop berdasarkan perspektif ekonomi Islam - Wulandari Wulandari; Suharli Suharli (Nur Science Institute, 2026)
This study aims to analyze how Electronic Word of Mouth (E-Wom) and information quality affect consumer purchase decisions on TikTok Shop, using the Islamic economic design framework developed by Adiwarman Azwar Karim. The research applied a quantitative descriptive approach, collecting data from 60 TikTok Shop users in Sungguminasa, Gowa Regency. The sample was selected using non-probability sampling. Data were gathered via Likert-scale questions and analyzed using multiple linear regression. The findings show that both partially and simultaneously, (E-Wom) and information quality had a positive and significant effect on purchase decisions, both individually and simultaneously. From the Islamic economics perspective of Adiwarman Azwar Karim, these results highlight the importance of upholding values such as honesty (shiddiq), information transparency (tabligh), trustworthiness (amanah), and justice (‘adl) in economic activities, including digital transactions and online marketing. This study also highlights the role of Electronic Word of Mouth and information quality in strengthening consumer trust toward halal products marketed through digital platforms.